Explore BrainMass

Explore BrainMass

    Derive Equation

    Not what you're looking for? Search our solutions OR ask your own Custom question.

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    Given the attached equation, mathematically prove the second equation ...

    © BrainMass Inc. brainmass.com December 24, 2021, 5:04 pm ad1c9bdddf


    Solution Preview

    Please see attached

    Problem #1


    Mathematically Prove that:


    p(x) = P(X = x)
    G(x) = P(X x) =

    I will use "Sigma (from x=0 to a)" for the Summation from x=0 to x=a and,
    "~" for Infinity.

    B(R) = Sigma (from x=R to ~) [x*p(x)] ...

    Solution Summary

    The solution mathematically proves the second equation